Study On The Extraction Of Ganoderma Lucidum Polysaccharides By Response Surface Analysis Two-phase Aqueous Extraction - Zhang Yinglong; Zhang Zhe; Xu Yuanxi; Ding Xinli; Wu Jiang; Jiang Haifang (BIO Web of Conferences, 2025)
In this paper, the extraction and separation of Ganoderma lucidum polysaccharide was carried out in the aqueous system of polyethylene glycol/ammonium sulfate for the first time. Using ganoderma lucidum mycelium as raw material, the effect of the concentration of phase forming substance on the partition coefficient of Ganoderma lucidum polysaccharide in the two-phase aqueous system was studied, and the lateral comparison was made with the traditional alcohol precipitation and hot water extraction of Ganoderma lucidum polysaccharide. The optimal ratio of polyethylene glycol and ammonium sulfate in the two-phase aqueous system was determined by the response surface design optimization experiment. The results show that when pH is 6.5, PEG6000 concentration is 16%, and ammonium sulfate concentration is 35%, the partition coefficient K of polysaccharide can reach 1.8-2.1. The study of this method provides a new method and idea for the extraction of Ganoderma lucidum polysaccharide in the future.